Beispiel Nr: 02
$ \text{Gegeben:}\\\text{Höhe} \qquad c \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \text{Oberfläche} \qquad O \qquad [m^{2}] \\ \\ \text{Gesucht:} \\\text{Breite} \qquad b \qquad [m] \\ \\ b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)}\\ \textbf{Gegeben:} \\ c=7m \qquad a=2m \qquad O=9m^{2} \qquad \\ \\ \textbf{Rechnung:} \\ b = \frac{O-2\cdot a\cdot c}{2\cdot (a+c)} \\ c=7m\\ a=2m\\ O=9m^{2}\\ b = \frac{9m^{2}-2\cdot 2m\cdot 7m}{2\cdot (2m+7m)}\\\\b=-1\frac{1}{18}m \\ \small \begin{array}{|l|} \hline c=\\ \hline 7 m \\ \hline 70 dm \\ \hline 700 cm \\ \hline 7\cdot 10^{3} mm \\ \hline 7\cdot 10^{6} \mu m \\ \hline 0,007 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline a=\\ \hline 2 m \\ \hline 20 dm \\ \hline 200 cm \\ \hline 2\cdot 10^{3} mm \\ \hline 2\cdot 10^{6} \mu m \\ \hline 0,002 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline O=\\ \hline 9 m^2 \\ \hline 900 dm^2 \\ \hline 9\cdot 10^{4} cm^2 \\ \hline 9\cdot 10^{6} mm^2 \\ \hline 0,09 a \\ \hline 0,0009 ha \\ \hline 9\cdot 10^{-6} km^2 \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline -1,06 m \\ \hline -10,6 dm \\ \hline -106 cm \\ \hline -1,06\cdot 10^{3} mm \\ \hline -1,06\cdot 10^{6} \mu m \\ \hline -0,00106 km \\ \hline \end{array}\\$